Doctoral Studies of Students in Educational Administration Programs in Non-Member UCEA Institutions - M. Scott Norton (Educational Considerations, 1992)
Doctoral studies in educational administration reflect considerable variation across the nation. Whether this is healthy or counterproductive is the subject of some debate.